Dealing with rent and rentier economies: New perspectives from institutional economics - Adrien Faudot; Julien Vercueil (Revue de la Régulation)
Heterodox economics may study rent from various angles. The first one is that of the source of income; the second is that of its macroeconomic impacts; the third is that of income distribution. This introduction highlights the contributions of the papers published in this issue from these three different angles. As far as it is concerned, Régulation Theory has developed a comprehensive reading of what it called the “rentier accumulation regime”, including it in the analysis of the variety of capitalism and allowing for a dialogue with development economics. In particular, it shows that institutional hierarchies co-evolve with the fluctuations of rent. The notion of rentier accumulation regime enables us to understand how some developing countries have resilient institutions despite structural weaknesses.